Еволюція удосконалення машин постійного струму та перспективи їх подальшого розвитку - Лущик, В'ячеслав Данилович; Варванський, Артем Юрійович (НТУ "ХПІ", 2011)
Пояснюється принцип дії машин постійного струму з неявнополюсним статором і несиметричною компенсаційною обмоткою, обгрунтовуються переваги цієї машини по енергетичним показникам та питомій витраті мідного проводу. Підкреслюються переваги двигунів постійного струму на транспортних машинах.

Operating principle for DC machines with a non-salient-pole stator and an asymmetrical compensation winding is explained. Advantages of these machines are grounded relative to power indexes and specific consumption of copper wire as compared with all other types of electric machines. Advantages of DC motors application in transport machines are underlined.
Evolution of dc machines improvement and prospect of their further development
Keywords: неявнополюсний статор; компенсаційна обмотка; мідний провод; транспортні машини; non-salient-pole stator DC machines; symmetrical compensation winding; power indexes